The RECONSTRUCTIVISM-BASED LEARNING IN MADRASAHS: RECONSTRUCTIVISM-BASED LEARNING IN MADRASAHS - Abd. Latif Manan (Maharah: Journal of Islamic Education Teaching and Learning, 2024)
This paper examines the integration of constructivist-based learning within Indonesia's education system, highlighting its transformative role in both Islamic and general educational settings. Grounded in Piaget’s cognitive development and Vygotsky’s sociocultural theories, constructivism emphasizes learner agency, prior knowledge, and context. The study explores how principles like active engagement and collaborative learning are applied, especially in Madrasahs, which blend Islamic teachings with general education to foster critical thinking and problem-solving. Constructivist practices, such as problem- and project-based learning, support authentic learning in a digital, multicultural landscape. Challenges include balancing learner-centered approaches with curriculum demands and overcoming resistance to pedagogical changes. By blending traditional Islamic values with modern educational needs, Madrasahs promote social responsibility and character growth. The study concludes that constructivist frameworks enhance student engagement and adaptability, contributing positively to Indonesia’s educational outcomes.